2014
DOI: 10.1016/j.jcrc.2014.02.017
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter population-based effectiveness study of teleintensive care unit–directed ventilator rounds demonstrating improved adherence to a protective lung strategy, decreased ventilator duration, and decreased intensive care unit mortality

Abstract: Implementation of teleICU-directed ventilator rounds was associated with improved and durable adherence to LPV and significant reductions in both VDR and ICU mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 17 publications
2
16
0
Order By: Relevance
“…Little formal investigation exists to describe and evaluate the effectiveness of PCUs ( 3 ). It is hypothesized that ICU services, bed utilization, and patient care outcomes may be positively impacted through use of PCUs ( 4 , 33 35 ); similarly Tele-ICU has shown to impact these factors positively ( 10 , 11 , 13 15 , 36 ) and therefore, Tele-PCU may also provide a distinct advantage. We found that PCU and hospital mortality rates were significantly lower for patients in TPCU group, compared with patients in NTPCUs.…”
Section: Discussionmentioning
confidence: 99%
“…Little formal investigation exists to describe and evaluate the effectiveness of PCUs ( 3 ). It is hypothesized that ICU services, bed utilization, and patient care outcomes may be positively impacted through use of PCUs ( 4 , 33 35 ); similarly Tele-ICU has shown to impact these factors positively ( 10 , 11 , 13 15 , 36 ) and therefore, Tele-PCU may also provide a distinct advantage. We found that PCU and hospital mortality rates were significantly lower for patients in TPCU group, compared with patients in NTPCUs.…”
Section: Discussionmentioning
confidence: 99%
“…Additional study characteristics are highlighted in e-Table 1 ( http://links.lww.com/CCX/A580 ). Seven of the included studies focused on the use of LTVV with definitions of LTVV varying by study ( 16 – 18 , 20 , 22 – 24 ). Two studies assessed the effect of an intervention on the use of prone positioning ( 19 , 20 ).…”
Section: Resultsmentioning
confidence: 99%
“…Seven of the included studies focused on the use of LTVV with definitions of LTVV varying by study ( 16 – 18 , 20 , 22 – 24 ). Two studies assessed the effect of an intervention on the use of prone positioning ( 19 , 20 ). Although all patients were mechanically ventilated, patient populations varied across studies as defined by the study authors including patients with primarily ARDS ( 18 , 19 , 21 ) or acute lung injury (ALI) ( 22 ), patients with ALI and ARDS ( 16 , 23 , 24 ), and patients with primary lung disease or complications of lung disease (including ARDS) ( 17 ) (e-Table 1, http://links.lww.com/CCX/A580 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…), glycemic control, and compliance with a strategy of lung-protective ventilation. 12 15 The benefits in this domain are perhaps expected, given that the tele-ICU models consistently provide immediate access to experts, who reinforce the importance of and ensure compliance with such quality improvement bundles.…”
Section: Models Of Tele-icu Care and Impact On Patient-important Outcmentioning
confidence: 99%